Civic ideology, organization, and law in the rule scrolls : a comparative study of the covenanters' sect and contemporary voluntary associations in political context - Gillihan, Yonder Moynihan (Leiden : BRILL, 2011)
Using insights from modern sociology, this book argues that the organization, law, and literature of the Dead Sea Scrolls sect expressed an "alternative civic ideology" by which members claimed citizenship in a superior commonwealth that would soon replace the existing Judean state.
Index of Modern AuthorsIndex of Ancient Sources.
Print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 082
Keywords: Dead Sea scrolls; Dead Sea scrolls; Civil society -- Palestine -- History; Jews -- History -- 586 B.C.-70 A.D.; Palestine -- Politics and government; Qumran community -- History; Religion and civil society -- Palestine; Religion and politics; Religion; RELIGION -- Judaism -- Sacred Writings; Civil society; Jews; Politics and government; Qumran community; Religion; Religion and civil society; Religion and politics; Middle East -- Palestine; 586 B.C.-70 A.D; Electronic books; History